1997
DOI: 10.1002/star.19970490705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Level on the Crystallinity of Wheat Starch Aged at Different Temperatures

Abstract: Differential Scanning Calorimetry (DSC) was used to study retrogradation of wheat starch. For storage at 4°C, enthalpy (ΔH) values of retrogradation endotherm (recrystallization) of wheat starch containing various moisture levels (25–80%) slowly continued to increase except in samples with moisture level of 50, 60 and 70%. For storage at 26°C and 32°C, most recrystallization of wheat starch occured within one and two weeks of storage time, while recrystallization with a moisture level of 50% at 26°C occurred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 12 publications
(7 reference statements)
2
12
0
2
Order By: Relevance
“…The peaks showed a trend shifting from higher gel-storage region to below 0°C as time increased. This was similar to the reported studies (Jang and Pyun, 1997;Ronda and Roos, 2008;Sandhu and Singh, 2007a) on retrogradation of wheat, potato and corn starches. The retrogradation onset temperatures appeared much lower than the former corresponded gelatinization temperatures.…”
Section: Buckwheat Flour Retrogradationsupporting
confidence: 92%
See 1 more Smart Citation
“…The peaks showed a trend shifting from higher gel-storage region to below 0°C as time increased. This was similar to the reported studies (Jang and Pyun, 1997;Ronda and Roos, 2008;Sandhu and Singh, 2007a) on retrogradation of wheat, potato and corn starches. The retrogradation onset temperatures appeared much lower than the former corresponded gelatinization temperatures.…”
Section: Buckwheat Flour Retrogradationsupporting
confidence: 92%
“…Water content (%) Temperature (°C) Enthalpy (J/g dry matter) (Jang and Pyun, 1997;Ronda and Roos, 2008;Ferrero and Zaritzky, 2000) that glass transition, recrystallization and a shift of peak would happen with elapse of time.…”
Section: Samplementioning
confidence: 99%
“…Jankowski & Rha (1986) observed that retrogradation endotherm of cooked wheat grains shifted to higher temperatures, when the storage temperature was increased from 4 to 20°C. Similar findings were reported by Jang & Pyun (1997) for wheat starch gels (4Q..60%) stored at 4 and 32°C. A study with rice starch gels (50%wlw) stored at different temperatures showed that, the extent of retrogradation followed the order: refrigerated> room temperature> frozen.…”
Section: Tg-glasstransitiontemperaturesupporting
confidence: 89%
“…Despite the numerous investigations that have been carried out to study retrogradation, the exact mechanism of retrogradation, particularfyatthe molecular level still remains unclear. The rate and extent of retrogradation is influenced by many factors such as botanical source (Orford at al., 1987;Jacobson et al, 1997), chain length of amylose and amylopectin (Gidley & Bulpin, 1989;Clark et al, 1989), water content in gel (longton & leGrys, 1981;, cooking and cooling conditions (Kimetal., 1993), storage temperature (Jankowski & Rha, 1986;Jang & Pyun, 1997) and the presence of solutes such as sugars, lipids and salts (Russell & Oliver, 1989;Katsuta et al, 1992a,b;Huang & White, 1993;Conde-Petit & Escher, 1994).…”
Section: Retrogradationmentioning
confidence: 99%
“…Generally, when starch suspensions are subjected to high temperature, the granules swell and rupture due to disruption of the amylopectin double helices (hydrogen bonds dissociation), while amylose preferentially leaches out from the swollen granules (Biliaderis, 2009). Starch retrogradation or staling, caused by re-crystallization of the polymer (dispersed amylose and amylopectin) chains, in baked foods occurs when gelatinized starch is cooled down and subsequently stored at low temperature (Jang and Pyun, 1997).…”
Section: Introductionmentioning
confidence: 99%